2012
DOI: 10.1093/ejcts/ezs178
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve surgery in patients who had undergone surgical myocardial revascularization previously

Abstract: Redo AVS performed in patients submitted to CABG previously results in mortality and morbidity rates that are much lower than what is expected, bringing clear benefits to the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The efficacy of surgical AVR in this setting can be compared to the much lower survival rates after TAVR (at two years 52–85%) . Indeed, two recent comparative analysis based on rather small series showed a trend toward better immediate survival after surgical AVR compared with TAVR and confirmed the low immediate mortality rates of recent surgical series reporting on immediate mortality rates below 7% . In previous series, AVR was performed along with other major cardiac procedures.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The efficacy of surgical AVR in this setting can be compared to the much lower survival rates after TAVR (at two years 52–85%) . Indeed, two recent comparative analysis based on rather small series showed a trend toward better immediate survival after surgical AVR compared with TAVR and confirmed the low immediate mortality rates of recent surgical series reporting on immediate mortality rates below 7% . In previous series, AVR was performed along with other major cardiac procedures.…”
Section: Discussionmentioning
confidence: 85%
“…Transcatheter aortic valve replacement (TAVR) has emerged as an alternative treatment in patients with a history of cardiac surgery now requiring aortic valve replacement (AVR) . However, recent reports suggested that surgical AVR can still be performed with good immediate and intermediate outcome in these patients . Patients with patent bypass grafts undergoing first‐time isolated AVR are increasing and represent multiple technical challenges.…”
mentioning
confidence: 99%
“…This less invasive approach appears particularly attractive for elderly patients with prior cardiac surgery to avoid extensive surgical trauma and injury to prior bypass grafts. However, recent reports suggest that AVR in patients with prior sternotomy may be safer than previously assumed [3,4] and risk models most likely overestimate surgical mortality. With wider acceptance of percutaneous techniques and enrollment of lower risk patients in TAVI trials [5], greater number of octogenarians with prior cardiac surgery are bound to be offered this form of therapy as mortality of redo surgical AVR in these patients has recently been reported at 12.8% [6].…”
mentioning
confidence: 94%